2018
DOI: 10.1038/s41566-018-0111-x
|View full text |Cite
|
Sign up to set email alerts
|

Giant multiphoton absorption for THz resonances in silicon hydrogenic donors

Abstract: The absorption of multiple photons when there is no resonant intermediate state is a non-linear process well known for atomic vapours, dyes and semiconductors. The N-Photon Absorption (NPA) rate for donors in semiconductors scales from hydrogenic atoms in vacuum proportionally with dielectric constant and inversely with effective mass -factors which carry exponents 6N and 4N respectivelyimplying extremely large enhancements are possible. We observed 1PA, 2PA and 3PA in Si:P with a THz free electron laser and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…It was reported that the 3PA coefficient is as large as 10 cm −1 (MW cm −2 ) −2 = 10 7 cm 3 GW −2 for hydrogen-like donors in silicon in the THz regime at 10 K. [19] Such an enormous 3PA coefficient is partially due to a hydrogenic oscillator scale being inversely proportional to ν 3 . [19] By considering the two-orders-of-magnitude difference between infrared and THz wave frequencies, the 3PA coefficient in the infrared is anticipated to be reduced by six orders of magnitude.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…It was reported that the 3PA coefficient is as large as 10 cm −1 (MW cm −2 ) −2 = 10 7 cm 3 GW −2 for hydrogen-like donors in silicon in the THz regime at 10 K. [19] Such an enormous 3PA coefficient is partially due to a hydrogenic oscillator scale being inversely proportional to ν 3 . [19] By considering the two-orders-of-magnitude difference between infrared and THz wave frequencies, the 3PA coefficient in the infrared is anticipated to be reduced by six orders of magnitude.…”
Section: Resultsmentioning
confidence: 98%
“…[19] Another way to increase α 3 , one may explore the electric dipole moment. In order to increase the 3PA coefficient, as shown by Equation (1), one may take advantage of a solid material with a large refractive index or dielectric constant, as a recent demonstration for a significant enhancement in MPA.…”
Section: Introductionmentioning
confidence: 99%
“…In addition narrow band gap semiconductors on Si offer opportunities for tunnelling enhancement in devices such as tunnelling-field effect transistors (TFETs) 12,13 for which GeSn is considered as a potential candidate system 14,15 . Also, Si has demonstrated enhanced nonlinear effects which is important for nonlinear THz applications 16 , and these nonlinear effects are expected to get stronger in narrow band gap materials such as GeSn and its alloys 17 . Due to recent advances in the growth of high crystalline quality GeSn and the diverse nature of its applications, the focus on GeSn alloys has gathered enormous pace 1823 .…”
Section: Introductionmentioning
confidence: 99%
“…From N th-order perturbation theory 7,11 the N-photon absorption (NPA) transition rate may be written aswhere , a B is the Bohr radius, E H the Hartree energy, and α fs the fine structure constant. M ( N ) is a dimensionless transition matrix element, and I m is the intensity of the light in the medium with relative dielectric permittivity ε r .…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding real part is responsible for a great variety of wavelength conversion processes such as harmonic generation, first observed in quartz 4 and later in atomic vapors 5 including alkalies 6 . THz multiphoton absorption has been shown to be very large in hydrogenic shallow impurities in semiconductors, even without intermediate state resonances 7 , due to the large dielectric screening and low effective mass. Here, we predict giant values for the real part of the THz non-linear susceptibility for doped silicon and germanium.…”
Section: Introductionmentioning
confidence: 99%